3D phase-resolved wave modelling with a non-hydrostatic ocean circulation model. (April 2019) - Marsaleix, Patrick; Michaud, Héloïse; Estournel, Claude
Abstract: A phase-resolved wave model is derived from an ocean circulation model for the purpose of studying wave-current effects in nearshore zones. One challenge is to adapt the circulation model to the specificities of wave physics. This mainly concerns the consideration of non-hydrostatic effects and the parametrization of wave breaking. The non-hydrostatic pressure is calculated using the artificial compressibility method (ACM). The ACM-induced errors on wave dispersion properties are examined in detail in the context of the linear theory using idealized test cases. The possible compromise between the precision achieved on non-hydrostatic physics and the adjustable CPU cost of the ACM method is looked at in detail. The modification of the wave characteristics by the bathymetric slope and the breaking of waves are then examined from a linear slope beach laboratory experiment. Finally the model is evaluated on the issue of rip currents and their feedback on the wave field using a laboratory experiment of a beach with a bar intersected by channels. Highlights: A 3D deterministic wave model is derived from a non-hydrostatic circulation model. The ACM method provides a compromise between precision and computational cost. Idealized cases highlight its ability to reproduce the characteristics of wave physics.